PENEGAKKAN HUKUM PIDANA TERHADAP IKLAN YANG MENYESATKAN DI WILAYAH HUKUM PENGADILAN NEGERI SAMARINDA - Abdul Munif (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The research objective was to determine the criminal liability against misleading advertising and law enforcement efforts against misleading advertising The experiment was conducted in the city of Samarinda, East Kalimantan province for 3 months. Research methods and techniques of research as follows: library research, field studies, and research papers.The results showed that: (1) the error is the principle of criminal responsibility adopted in Indonesia. Without the error on the creator himself, then it can not be criminal to him. Due to convict the perpetrator must be a mistake first. Liability which may be imposed against misleading advertising is to prove that there is an error on the sellers, advertising agencies and the media. So that they can be punished. Evidentiary difficulties faced, the necessary accountability necessary to deviate from the principle of error. With the application of the principle of accountability strict liability, vicarious liability and enterprise liability in the upcoming draft new Penal Code, then to ask the perpetrators to justice will not have problems, and (2) efforts as law enforcement against misleading advertising are: (a) implement the provisions of and sanctions that exist both in the Criminal Code and the law on Consumer Protection, (b) a sanction imposed should be firm and clear to be implemented, and (c) the Law in order to be effective, those who work as law executors should discharge their duty properly -good. They should use the law broadly. They must be interpreted uniformly and with the certainty that fixed.